2007
DOI: 10.1001/archopht.125.10.1381
|View full text |Cite
|
Sign up to set email alerts
|

Optic Neuritis Associated With Chikungunya Virus Infection in South India

Abstract: Objective: To define optic neuritis associated with chikungunya virus (CHIKV) infection in a clinical setting. Methods: This observational case series includes 14 patients with clinical features of CHIKV infection and associated optic neuritis. Complete ophthalmic evaluations were performed, as well as other examinations, including Mantoux test, Widal test, blood profile, color vision, neuroimaging, visual fields, visual evoked potentials, VDRL test, and enzyme-linked immunosorbent assay for CHIKV-specific imm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
75
0
5

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(84 citation statements)
references
References 19 publications
1
75
0
5
Order By: Relevance
“…viruses, such as chikungunya (19)(20)(21), dengue virus (DENV) (22)(23)(24), and West Nile virus (WNV) (25,26), in adults, including optic neuritis, retinal hemorrhages, and retinal edema. Therefore, it is highly unlikely that the microcephaly itself causes retinal abnormalities.…”
Section: Introductionmentioning
confidence: 99%
“…viruses, such as chikungunya (19)(20)(21), dengue virus (DENV) (22)(23)(24), and West Nile virus (WNV) (25,26), in adults, including optic neuritis, retinal hemorrhages, and retinal edema. Therefore, it is highly unlikely that the microcephaly itself causes retinal abnormalities.…”
Section: Introductionmentioning
confidence: 99%
“…Other classical symptoms of CHIKV infection include febrile illness (temperature usually .38.9˚C), maculopapular rashes, myalgia, headache, edema of the extremities, and gastrointestinal complaints (10,11). In some cases, CHIKV complications, such as acute nephritis (12), myocarditis, pericarditis (13), myopericarditis (14), retrobulbar neuritis (15), neurologic complications, and death, have also been reported (16,17).…”
mentioning
confidence: 99%
“…A delay of more than two weeks has been reported with other complications like myelitis, GBS, and optic neuritis 13,17,21 . A prospective study, performed in India from August to October 2006, of 20 hospitalized patients, found the occurrence of neurological symptoms and signs early in the course of the disease in cases of Chikungunya.…”
Section: Confirmed Cases Of Zikamentioning
confidence: 98%
“…Neurological complications described in the recent epidemics include: meningo-encephalitis, meningoencephalo-myeloradiculitis, myeloradiculitis, myelitis, myeloneuropathy, Guillain-Barré Syndrome (GBS), external ophthalmoplegia, facial palsy, sensorineural deafness, and optic neuritis 13,14,15,16,17,18,19,20,21,22,23 . Optic nerve involvement in CHIKV infection includes papillitis, retrobulbar neuritis, and neuroretinitis 17 .…”
Section: Clinical and Neurological Manifestationsmentioning
confidence: 99%
See 1 more Smart Citation